STUDI TENTANG MONUIMEN ILYAS JACOUB DI KENAGARIAN PAINAN DITINJAU DARI NILAI ESTETIKA - Yoki Riswandi, Dr. Ramalis Hakin, M.Pd., Drs. Eswendi, M.Pd. (Serupa The Journal of Art Education, 2017)
This study uses a qualitative methodology with descriptive research, which describe everything that was found in the field according to the research objectives and reality. Descriptive method aims to describe or analyze the results of the study but not used to make broader conclusions. The results showed that the objective aesthetic value in the form of artwork that has beauty looks naked eye so it looks nice, attractive colors, furnished garden and situated in a strategic location. While the subjective aesthetic value Ilyas Jacoub monument in the form beauty of art is not only the physical elements that are absorbed by the eye visually, but is determined by the tastes of the audience. It turned out that the subjective aesthetic value Ilyas Jacoub monument was mediocre and nothing interesting artistic elements thereKata Kunci: Monumen Ilyas Jacoub, Nilai Estetika